Comparison of primary care prescriptions for old and very old hypertensive patients - KAŞKAL, MERT; AKICI, AHMET (My University, 2023)
Background/aim: Elderly and very elderly individuals might be subject to different approaches for the treatment of hypertension. We aimed to compare drug utilization in hypertensive old patients and very old patients in primary care, along with the evaluation of potentially inappropriate drug prescribing. Materials and methods: In this cross-sectional study, we compared prescriptions of 65–79-year-old (old patient prescriptions [OPP], n = 433,988) vs. ≥80-year-old (very old patient prescriptions [VOPP], n = 134,079) with \"essential hypertension\" diagnosis, issued by 3:1 systematically-sampled primary care physicians (n = 1431) in İstanbul throughout 2016. Drug utilization patterns and distribution of antihypertensives based on drug class and combination status were evaluated. Frequency of potentially inappropriate drugs per Beers Criteria were identified and compared. Results: Antihypertensive monotherapy practice was less common in OPP than VOPP (43.3% vs. 45.3%; p < 0.001). In both groups, the most commonly prescribed drugs were beta-blockers for monotherapy (37.4% vs. 33.1%, p < 0.001) and thiazide diuretics for combined therapy (69.8% vs. 67.4%, p < 0.001). Metoprolol was the most commonly prescribed antihypertensive both in OPP and VOPP (15.3% vs. 14.8%). Furosemide was ranked 10th in OPP and 3rd in VOPP (2.7% vs. 5.5%). Cardiovascular system drugs were the most commonly encountered potentially inappropriate medications in both groups (263.9 vs. 283.4 per 10,000 prescriptions, p = 0.004). Regarding antihypertensive drugs, 2.2% of those in OPP and 2.4% of those in VOPP were identified as potentially inappropriate (p = 0.002). Conclusion: Prescribing preferences to old and very old patients mostly showed slight differences. Almost half of prescriptions comprising antihypertensive monotherapy might imply hesitancy to prescribe combinations. Overuse of risky drugs such as furosemide in both groups, especially in the very elderly, requires more attention.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Elderly; family physician; irrational prescribing; hypertension; BETA-BLOCKERS; ADULTS; MANAGEMENT